In vitro anti-oxidation, anti-hepatic steatotic and anti-inflammatory effects of Auricularia nigricans (SYN A. polytricha) / Teoh Hoe Leong - Teoh , Hoe Leong (2020)
At present, non-alcoholic fatty liver disease (NAFLD) is one of the most frequent liver diseases worldwide. In general, NAFLD is asymptomatic, and can slowly progress to serious complications such as cirrhosis, hepatocellular carcinoma, cardiovascular disease and death. Although there are no approved treatment regimens for NAFLD at this moment, lifestyle modifications through diet is the mainstay of treatment. Auricularia nigricans is a popular edible mushroom known to possess medicinal properties such as antioxidant, antitumor and anti-inflammatory. The present study was conducted to determine the beneficial effects of A. nigricans against NAFLD through investigation of the in vitro free radical scavenging activities, anti-inflammatory capacity, hypolipidemic effect and mechanism triggered by bioactive fractionated samples from A. nigricans towards palmitic acid-induced HepG2 cells. Evaluation of total phenolic content in ethanolic crude, hexane, ethyl acetate and water fractions from A. nigricans indicated that ethyl acetate fraction was found significantly higher than other fractions (p<0.05). Furthermore, ethyl acetate fraction showed the strongest scavenging peroxyl, hydroxyl, DPPH radicals effects. In addition, ethyl acetate fraction also demonstrated significant high capacity in ferric reducing antioxidant power (FRAP). Among all, water fraction was the only fraction capable of scavenging all radicals tested. Therefore, ethyl acetate and water fraction were subjected to gas chromatography mass spectrometry and liquid chromatography mass spectrometry analysis for assessing the bioactive compounds profile. Linoleic acid ethyl ester, Butyl 9,12-octadecadienoate, 9,12-Octadecadienoic acid, Ergosta-5,7,22-trien-3-ol, 2(3,4-Dihydroxyphenyl)-7-hydroxy-5-benzene propanoic acid and 3,30-di-O-methyl ellagic acid were identified in the ethyl acetate fraction, while oxooctadecanoic acid and 2(3,4-dihydroxyphenyl)-7-hydroxy-5-benzenepropanoic acid were identified in the water fraction. 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide (MTT) assay showed that water fraction was non-cytotoxic to HepG2 cells, whereas ethyl acetate fraction was cytotoxic to HepG2 cells at 100 μg/mL. Assay on anti-hepatic steatotic, ethyl acetate fraction showed significant inhibitory effects on lipid accumulation (p<0.05), but not water fraction. Furthermore, ethyl acetate fraction exhibited significant capacity (p<0.05) in attenuating intracellular reactive oxygen species (ROS) level, but not water fraction. Hence, the anti-inflammatory effect of ethyl acetate fraction was investigated. Co-incubation of 25 and 50 μg/mL ethyl acetate fraction with palmitic acid, markedly decreases tumour necrosis factor alpha (TNF-α), intereukin-6 (IL-6), interleukin-8 (IL-8) and monocyte chemoattractant protein-1 (MCP-1) levels. Both concentrations also showed no significant different in the reduction of pro-inflammatory cytokine levels. Further investigation of antioxidant and anti-inflammatory effects at signalling pathway using palmitic acid-induced HepG2 cells co-incubated with 25 μg/mL ethyl acetate fraction showed suppression of stress-activated protein kinases/jun amino-terminal regulated kinases (SAPK/JNK), p-38 mitogen-activated protein kinases (p-38 MAPK), nuclear factor-kappa B (NF-κB) and signal transducer and activator of transcription 3 (STAT-3) signalling pathways. In conclusion, the present findings suggest that A. nigricans demonstrated anti-steatotic effects that involved antioxidant capacity, hypolipidemic effect and anti-inflammatory capacity in the palmitic acid-induced NAFLD pathological cell model. Combined together, ethyl acetate fraction shows potential to be used in the development of anti-hepatic steatotic agent and A. nigricans may be considered to be promoted to be used in diet intervention for NAFLD and NASH patients. Keywords: